PERANAN LINGKUNGAN BAHASA DALAM PEMEROLEHAN BAHASA KEDUA - Purba, Andiopenta (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
Language is a certain place and circumstance where a language expanded used by the speech community. It consists of everything that can be heard and seen, then, it influences the process of language communication. Language environment can be divided into two categories: formal setting, which is formed by planning, and informal setting,  which  is  formed  naturally.  Formal  setting  has  important  role  in  second language  acquisition  process,  especially  in  the  sequence  of  second  language acquisition,  and  the  succes  acceleration  of  second  language  acquisition. Furthermore,  informal  setting  has  important  role  in  second  language  acquisition process, especially in the learner’s peer environment, parents, family, and foreign speaker environment.Key words: second language acquisition, language environment